ANALISIS MANAJEMEN PEMELIHARAAN DAN PERAWATAN BANGUNAN RUSUNAWA BERDASARKAN PERMEN PU NO.24/PRT/M/2008 (RUSUNAWA PINUS ELOK BLOK A) - Wahyu Hidayat; Anisah Anisah; Rosmawita Saleh (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2020)
Research aims to analyze maintenance and repair management of Simple Rental Apartment building based on Regulation of Minister of Public Works No.24 / PRT / M / 2008 on guidance of procedure and method of maintenance and repair of building. The rise of vertical government-built residential development is not matched by adequate maintenance management. This research was conducted by analyzing maintenance management to managers, technicians and cleaning service by using interview guides and checklist of conformity table based on Regulation of Minister of Public Works No.24 / PRT / M / 2008.Results of this study states that not maximal maintenance management undertaken Simple Rental Apartment managers. The result of research also found that the suitability level of the method from the observation result the researcher only got percentage of 32% based on Regulation of Minister of Public Works No.24 / PRT / M / 2008.